A review of bevacizumab in the treatment of malignant pleural mesothelioma. (December 2017) - Brosseau, Solenn; Assoun, Sandra; Naltet, Charles; Steinmetz, Christelle; Gounant, Valérie; Zalcman, Gérard
Malignant pleural mesothelioma (MPM) is an aggressive cancer with poor prognosis. Systemic chemotherapy is the primary treatment modality for the majority of patients. VEGF plays a key mitogen for MPM cells physiopathology. Bevacizumab, a monoclonal anti-VEGF antibody, was a rational approach to be tested in MPM. Based on the results of the Phase III IFCT-0701 mesothelioma avastin cisplatin pemetrexed study, cisplatin-pemetrexed-bevacizumab is now the accepted standard in France. The National Comprehensive Cancer Network guidelines have also included this combination as an option for standard front-line therapy. This review summarized the efficacy and safety data of bevacizumab in the treatment of patients with MPM.